PLASTIC DEFORMATION OF GRAPHITE WHILE HEATING COMPOSITE POWDERS - V. N. Kovalevsky; A. E. Zhuk; I. V. Fomikhina; A. V. Kovalevskaya; S. V. Grigoriev; A. V. Rulkevich (Наука и техника)
The paper presents results of graphite surface morphology research and graphite structure improvement (density increase) in nano-coatings of iron alloy powders while making isothermal heating up to 1200 °С and plastic deformation caused by tensile stress due to significant difference in iron and graphite thermal expansion coefficients. Framework structure formation of squeezed graphite on iron-group metal particles makes it possible to obtain composite powders for preparation of erosion-resistant composite materials.